Efektivitas Penggunaan Chatbot AI sebagai Media Pembelajaran Interaktif terhadap Keterampilan Logika Pemrograman Siswa SMK Kelas 12 TKJ - ramadani, sinta; Vitriani, Vitriani (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2025)
Artificial Intelligence (AI) is a technology that can think like humans that is run by robots that are not natural from humans themselves. One of the increasingly popular applications of AI technology is chatbots, which are computer programs designed to communicate with humans naturally and responsively. In the context of vocational education, especially in vocational schools majoring in Computer Engineering and Networks, programming logic skills are one of the competencies that students must have. Various studies show that many vocational school students have difficulty understanding the concept of programming logic. This satisfaction is often caused by the limited innovative learning media that can explain concepts in an adaptive way according to student needs. Therefore, this study aims to highlight the extent to which the use of AI-based chatbots can participate in improving the programming logic skills of 12th grade vocational school students majoring in TKJ. The use of AI chatbots as interactive learning media has proven effective in improving the programming logic skills of 12th grade vocational school students majoring in TKJ.